NEITHER WITH YOU, NOR WITHOUT YOU. POPULAR LIBRARIES, CULTURAL ASSOCIATIONISM AND PUBLIC ACTION IN THE SOUTHWEST OF THE PROVINCE OF BUENOS AIRES (1880-1930) - Agesta, María de las Nieves (Revista de Historia Social y de las Mentalidades, 2024)
This paper examine three popular libraries in the southwest of the province of Buenos Aires (Argentina), founded between the end of the 19th century and the beginning of the 20th century by different groups that shared, however, their confidence in the power of written culture as a factor of civilization in locations recently integrated to the national state consolidation project. In this sense, it is intended to analyze the complex relationships established by these libraries with the public authorities and their bureaucratic agencies at the national, provincial and municipal levels, paying particular attention to the tensions generated between their claim of autonomy and the demands for financing and official endorsement required to ensure continuity and expansion of their cultural work.
Keywords: Popular Libraries; Cultural Associations; State; Regional History